2021
DOI: 10.1108/ijlm-12-2020-0486
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders conflict and private–public partnership chain (PPPC): supply chain of perishable product

Abstract: PurposeThis paper aims to address procurement, logistics management, inventory control and distribution of perishable items, i.e. vegetables, fruits, flowers and fishes, during the social isolation period of the Covid-19 era to identify conflicting interests among the channel members; present inventory and information sharing scenario; and reveal organizational dispute and existence of redundant, nonessential and corrupted members in the supply chain.Design/methodology/approachThis study uses an exploratory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 125 publications
2
10
0
Order By: Relevance
“…These complement research findings by Gonzalez-Torres et al (2021) who revealed that such a self-interest seeking attitude by business partners during the Covid-19 pandemic was responsible for reducing their financial performance. It also reinforces recent findings by Shareef et al (2022) that the Covid-19 crisis has given rise to unethical practices by some firms in an attempt to gain more benefits than deserved from their partners (and in some cases from end-customers), thus creating bitter feelings.…”
Section: Discussionsupporting
confidence: 86%
“…These complement research findings by Gonzalez-Torres et al (2021) who revealed that such a self-interest seeking attitude by business partners during the Covid-19 pandemic was responsible for reducing their financial performance. It also reinforces recent findings by Shareef et al (2022) that the Covid-19 crisis has given rise to unethical practices by some firms in an attempt to gain more benefits than deserved from their partners (and in some cases from end-customers), thus creating bitter feelings.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, withstanding and recovering from the current threats of the pandemic and establishing a resilient supply chain for the tourism and hospitality service is fundamentally rooted in the design of an innovative facility as the supply chain driver. This finding is well supported by many scholars (Hall et al 2020 ; Lengnick-Hall et al 2011 ; Nilakant et al 2014 ; Shareef et al 2021a ) working on the destructive impact of the current pandemic on tourism and hospitality service and the successive recovery procedures. Some researchers (Mittal and Sinha 2021 ; Ngoc Su et al 2021 ) have suggested that to design a well-equipped facility that can provide satisfactory and adaptable features meeting the new expectations of tourists to fight against all the negative consequences of the pandemic based on their experience, is not only crucial but also could be a vulnerable issue and the most challenging task faced by tourism and hospitality companies.…”
Section: Findings and Interpretation Of The Study Data And Supply Cha...supporting
confidence: 53%
“…First, the findings of a qualitative case study add knowledge to supply chain resilience literature and suggest developing resilience. While the theory around supply chain disruptions and supply chain resilience have been evolving separately (Ali et al , 2018; Hobbs, 2020; Ivanov et al , 2019; Shareef et al , 2021; Sharma et al , 2020a, b; Singh et al , 2020), research on integration of these topics is limited. Consequently, the primary contribution of the study is to understand various types of supply chain disruptions, role of supply chain resilience in mitigating the severity of the impact of these disruptions and practices applied to develop resilience capability in an agricultural food supply chain.…”
Section: Discussionmentioning
confidence: 99%
“…In the last one and a half years, the COVID-19 pandemic has severely impacted and continues to impact the ways production, distribution and consumptions of agri-food are being managed worldwide (Barichello, 2020; Hobbs, 2020; Narayanan and Saha, 2020). Because of this unforeseen and unprecedented situation, food and beverage firms are facing significant challenges, both in terms of disrupted supply and reduced consumption (Chowdhury et al , 2020a, b; Hobbs, 2020; Shareef et al , 2021). With prolonged lockdown and prohibition on several goods and services, the agriculture food supply chain grappled with solving several supply-side and the demand-side issues (Brewin, 2020; Sharma et al , 2020a, b).…”
Section: Introductionmentioning
confidence: 99%